Class conditioning and class positioning in young people's everyday life with digital media - Danielsson Martin (Nordicom Review)
In this article, I explore how social class shapes the conditions and configurations of digital media practice in the everyday life of young people in Sweden. Drawing on Bourdieusian theory and qualitative interview data from two research projects, I complicate the notion of Sweden as a universally wired media welfare state by showing how economic and cultural forces are structuring Internet access and digital media practice along the lines of preexisting social divisions. Invoking Bourdieu's conceptualisation of social classes as defined both intrinsically and relationally, I identify and exemplify two different but interrelated processes whereby class makes a difference in young people's everyday relationship to digital media: class conditioning and class positioning. I conclude the article by arguing that distinguishing between these processes might offer a better understanding of the relationship between class and everyday media practice. The complexities of advancing a welfare-oriented media policy in the age of digital media are also discussed.